(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article explains the concept of culture, cultural institutions, spiritual and aesthetic needs, the concept of national spiritual heritage, language, lifestyle, mentality, customs, music, theater, ensembles, education and attitudes towards women, the specific culture of the Surkhandarya people. existence, attitude to culture, differences in attitude to culture depending on the form of worldview, antiquity of Surkhan oasis culture, study of culture of our people, misunderstanding of our nationality in the period of tsarism, dictatorship, development of national culture of our people.